Adenocarcinoma polimorfo de baixo grau de malignidade do tipo papilífero. Estudo morfológico e imuno-histoquímico. - Carvalho, Y. R.; de Oliveira Nogueira, T.; de Souza, S. O.; de Araujo, V. C. (My University, 1990)
Two cases of polymorphous low-grade adenocarcinoma of the papillary type, from minor salivary glands were studied by light microscopy and immunohistochemistry. One case exhibited a predominance of the papillary pattern, whereas the other presented the following patterns of histological appearance: papillary, solid, pseudocystic and tubular. Utilizing the peroxidase-antiperoxidase (PAP) method, the intermediate filament vimentin, keratin and S100 protein were observed in tumor cells. The immunohistochemical analysis revealed two types of neoplastic cells: myoepithelial and luminal.
Low-grade polymorphic adenocarcinoma of papillary type. Morphological and immunohistochemical study
Keywords: keratin; protein S 100; tumor protein; vimentin; adenocarcinoma; adult; case report; chemistry; female; human; immunohistochemistry; male; minor saliva gland; pathology; salivary gland tumor; Adenocarcinoma, Papillary; Adult; Case Report; English Abstract; Female; Human; Immunohistochemistry; Keratin; Male; Neoplasm Proteins; S100 Proteins; Salivary Gland Neoplasms; Salivary Glands, Minor; Vimentin